Confronting the Truth: The Necessity of Love for Justice - Paradise, Brandon (Journal of law and religion, 2022)
This essay examines the interplay between law, Christianity, and oppression in the thought of James Baldwin. This essay begins its inquiry from Baldwin's own essay, Equal in Paris, and expands out to his broader writing. The essay makes four contributions. First, it shows that Equal in Paris presents a view of law and Christianity as simultaneously serving as instruments and sources of hypocrisy and injustice while representing critically important, if difficult to achieve, standards of justice and love. Second, the essay shows that for Baldwin avoidance and denial of collective moral failure underlies the hypocritical use of law and Christianity to perpetrate injustice rather than justice. Third, the essay reveals that Baldwin would see current legislative bans of critical race theory as a means of avoidance and denial of collective moral failure. Moreover, from a Baldwinian perspective, the maintenance of innocence through bans on critical race theory is a "crime" that typifies the problem at the root of racial oppression in America, which is the refusal to come to terms with the reality of white supremacy. Fourth, while agreeing with scholars who find significant overlap between Baldwin’s approach to law and critical race theory, the essay concludes that Baldwin’s work suggests that critical race theory's neglect of love constitutes a critical shortcoming for critical race theory's anti-subordinationist agenda.